Pengaruh Motivasi Kerja, Lingkungan Kerja dan Pengembangan Karir Terhadap Kepuasan Kerja Karyawan - Erina Rulianti; Giri Nurpribadi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
Human resources is very important in a company. therefore every company always strives to have quality human resources and the company should pay attention to aspects of work related to human resources, because without quality human resources a company will not work well between HR and the company must have a relationship that needs each other, the company need quality employees, employees also need a work environment that can provide satisfaction such as having a clean and comfortable work environment, one of the company's activities to advance the capabilities of its employees is employee career development and provide motivation to employees from research is to determine the influence of motivation, environment work and career development on job satisfaction of employees of PT. Daelim Indonesia jababeka 2. This research is included in the category of quantitative research. The total population is 300 employees, so the sample used is 75 employees because it uses the Slovin formula. From the results where work motivation, work environment and career development have an effect on job satisfaction.